The Influence of Work Environment on Employee Performance at PT. Rejeki Bukit Separi - Nurasih, Denok Intan; Karhab, Rinda Sandayani; Jubaidi, Jubaidi (Asosiasi Ahli Administrasi Indonesia, 2025)
Rejeki Bukit Separi is a labor supply company for the coal mining industry in East Kalimantan. This study employs a quantitative approach using survey techniques, involving the entire population of 66 employees as the sample through total sampling. The analytical techniques used include validity tests, reliability tests, classical assumptions, and simple linear regression tests using SPSS version 25. The results of the study indicate that the physical work environment significantly influences performance. The objective of this study is to analyze the influence of the work environment on employee performance at PT. Rejeki Bukit Separi. Specifically, this study aims to identify the extent to which aspects of the work environment, both physical and non-physical, such as safety and social relationships, play a crucial role in supporting employee productivity and work effectiveness. Therefore, companies need to prioritize workplace environment quality as a strategic component of human resource management, especially in the mining sector, which is characterized by operational challenges and high work-related risks. These findings not only provide practical contributions for company management in designing policies more focused on employee well-being but are also expected to serve as a reference for further research and contribute theoretically to the development of human resource management science, particularly in the labor-intensive sector.